2015
DOI: 10.1016/j.sbspro.2015.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Visual Wine Metaphor and Metonymy in Ads

Abstract: The aim of advertising is to persuade consumers to buy a product or service. A distinct feature of advertising is its reliance on pictures to achieve this aim. Many ad images encode a metaphor. In this paper we posit the view that visual metaphor relies upon perceptual similarity, conceptual similarity, or in the combination of both types. We shall examine the ways in which visual metaphors in Spanish ads for wines are construed on the basis of formal and conceptual criteria. Two issues will be addressed: (i) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
3
8
0
2
Order By: Relevance
“…In the case of Daily political cartoons, our results are in line with those of many scholars who claim that the link between the referenced and fictional situations in political cartoons is achieved by means of metaphors (see El Refaie 2003Shelton Caswell 2004;Steuter & Wills 2011;Negro Alousque 2013, 2014. Referenced situations usually involve abstract concepts and metaphor is very conducive to represent such concepts in a more familiar way.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the case of Daily political cartoons, our results are in line with those of many scholars who claim that the link between the referenced and fictional situations in political cartoons is achieved by means of metaphors (see El Refaie 2003Shelton Caswell 2004;Steuter & Wills 2011;Negro Alousque 2013, 2014. Referenced situations usually involve abstract concepts and metaphor is very conducive to represent such concepts in a more familiar way.…”
Section: Discussionsupporting
confidence: 89%
“…In-depth studies about how different rhetorical resources cooperate are scarce. Some contributions are focused on the interaction between metaphor and metonymy (Goossens 1990;Ruiz de Mendoza Ibáñez & Mairal Usón 2007;Negro Alousque 2013;Ying-Yu Lin & Chiang 2015) and some others offer a general panorama (Pedrazzini & Scheuer 2012). In this particular research about political cartoons, we observed an association between irony and sarcasm and other figures of thought such as allusion operating in the verbal mode.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Against this background, many studies have focused on the use of visual metaphor in specialized language, including economics (Rojo López & Orts Llopis, 2010), political cartooning, and advertising (Negro Alousque, 2015), but studies that examined the use of monomodal and multimodal metaphors in memes, especially in an Arab context, are scarce to the best of the researchers’ knowledge (see Younes & Altakhaineh, 2022). Note also that CMT or one of its updated versions, for example, main meaning focus, has been adopted as theoretical framework by many recent studies (e.g., Al-Saleh et al, 2020; Zibin, 2021).…”
Section: Theoretical Framework and Previous Studiesmentioning
confidence: 99%
“…ExxonMobil also attempts to appraise and exalt the state by using propositions such as Energy lives here and [Akwa Ibom is] the land of promise. The Subject, Energy, operates as metonymy and in the form of an animated being (ALOUSQUE, 2015;PÉREZ-SOBRINO, 2016). In a sense, Energy represents petroleum resources, while the "fused" Finite-Predicator, lives, extols Energy as an animate entity.…”
Section: Textmentioning
confidence: 99%